A243 AN UNCONVENTIONAL CASE OF OLMESARTAN ASSOCIATED ENTEROPATHY. (1st March 2018) - Ghaith, J; Szilagyi, A
Abstract: Background: While chronic diarrhea is costly, drug-induced enteropathy is a treatable etiology if identified. Olmesartan has been reported to cause chronic diarrhea since 2012. There are approximately 200 cases reports/series linking Olmesartan with observed villous atrophy on duodenal biopsies. It is essential to recognize that OAE is a differential diagnosis in cases of refectory celiac disease and it's severity ranges through a spectrum of clinical and histolpatholigcal findings. In our report, we identify a case of OAE based on clinical symptom with preserved villous architecture on small bowel biopsy. Aims: - To report a clinical case of OAE with preserved villous architecture on duodenal biopsy and modestly elevated serologic markers of Celiac Sprue. - To increase awareness among clinician of OAE; a new missed differential of sprue-like enteropathy. Methods: We present a clinical case of chronic worsening severe diarrhea encountered in gastrointestinal outpatient clinic followed up from January 2017 to September 2017. Results: A 62- years-old female patient known for hypertension and Irritable Bowel Syndrome-D for 8 years presented in late 2016 with worsening persistent diarrhea. Work up including colonoscopy with biopsies and MRI Enterography was negative. Serologically, carcinoid and infectious etiology were also negative. However, transglutaminase antibody (IgA TTG) levels were modestly elevated (45U/ml - April 2017 then 19 U/ml- May 2017, N < 9U/ml). An earlier IgA TTG was negative in 2010. On the contrary, small bowel biopsies exhibited preservation of villous architecture with increased CD3+ intraepithelial lymphocyte (MARSH 1A). Therapeutic trials including gluten free diet (GFD) for 3 weeks, antibiotics, and corticosteroids failed. Supportive medications loperamide had modest benefit. Finally, on review of medication, patient was noted to be on Olmitec R (Olmesartan), and soon upon the cessation of the medication, patient reported improved bowel habits. Conclusions: Drug-induced enteropathy is a frequently missed differential for chronic diarrhea. Almost all previously reported cases depicted histological evidence of villous atrophy along with mucosal inflammation with recovery upon cessation of Olmesartan or other offending ARBs. Our case report has identified OAE presenting as celiac mimicker but without clinical response to GFD. OAE can be a difficult entity to diagnose in the setting of equivocal histological findings. Olmesartan can inflict a spectrum of intestinal injury ranging from mild lymphocyte infiltration to severe villous atrophy. Clinical judgment and careful medication review should be applied to distinguish celiac from drug-associated enteropathy. Funding Agencies: None